A comprehensive review of Shengdeng in Tibetan medicine: textual research, herbal and botanical distribution, traditional uses, phytochemistry, and pharmacology - Ma, Jing; Li, Qiuyue; Wang, Ting; Lu, Hanyu; Liu, Jia; Cai, Rangji; Zhang, Yi; Zhang, Jing; Xie, Xiaolong; Su, Jinsong (Frontiers in Pharmacology, 2023)
Shengdeng‖ (སེ ང་ལེ ང་།), a group of Tibetan medicines with diverse biological origins, has long been utilized in Tibet for the treatment of rheumatoid arthritis. It showcases remarkable efficacy in alleviating rheumatism, reducing swelling, and relieving pain.This study aimed to clarify the plant species used as -Shengdeng‖ and summarize their botanical distribution, traditional uses, phytochemistry, and pharmacology to promote its utilization and development. -Shengdeng‖ is derived from a remarkable collection of 14 plant species belonging to six distinct families. Extensive phytochemical investigations have led to the identification of 355 chemical constituents within -Shengdeng‖. Pharmacological studies conducted on -Shengdeng‖ have revealed a wide range of beneficial properties, including antioxidant, anticancer, antimicrobial, antiviral, antiparasitic, anti-inflammatory, and anti-arthritic activities.Notably, flavonoids and triterpenoids emerge as the predominant groups among these constituents, contributing to the therapeutic potential and diverse applications of -Shengdeng‖.The present review provides a concise summary of the recent advancements in textual research concerning the herbal and botanical distribution, traditional uses, phytochemistry, and pharmacological activities of -Shengdeng‖. It is crucial to note that future research on -Shengdeng‖ should prioritize the analysis of its active ingredients and the establishment of rigorous quality standards. These aspects are essential for ensuring consistency, efficacy, and safety in its clinical application.